Eye-tracking as a measure of receptive vocabulary in non-verbal children with cerebral palsy - Susheel Joginder Singh; Suvalaxmi Raman; XinTong Lim; Vinitaa Rajakumar; Rogayah A. Razak; Shin Ying Chu (PLoS ONE, 2025)
Children with cerebral palsy (CP) often struggle to participate in traditional language assessments due to their limited mobility, making it challenging for speech-language therapists (SLTs) to accurately assess their language abilities. In recent years, there has been evidence that eye-tracking is an effective way of measuring the receptive language abilities of children who demonstrate difficulties with traditional language assessments. This study aimed to (i) develop eye-tracking assessment materials based on a receptive vocabulary subtest of a Malay language assessment and (ii) evaluate the performance of children with CP on the receptive vocabulary assessment conducted via eye-tracking, compared to their performance on a traditional receptive vocabulary assessment. The first phase of the study focused on developing eye-tracking receptive vocabulary assessment materials from the Malay Preschool Language Assessment Tool and trialling the materials and assessment protocol. This phase involved 15 typically developing children aged 4–6 years. The finalized materials and protocol were administered to 15 children with CP in the second phase. Each child attended two assessment sessions: the first was a traditional receptive vocabulary assessment, and the second utilized eye-tracking technology. Children practiced eye-tracking through online games. Results showed that eight children with CP performed better in the eye-tracking assessment, two scored similarly across both methods, and five scored lower during eye-tracking. The Wilcoxon Signed Rank Test conducted revealed no significant difference in scores across both assessment methods (p > .05). Furthermore, most children exhibited poor consistency in their scores across the two methods. These findings suggest that while some children with CP may benefit from receptive vocabulary assessments conducted via eye-tracking, no single assessment method is optimal for all children with CP. Instead, children with CP may benefit from a combination of assessment methods, including eye-tracking, to increase the accuracy of assessment results.